2015
DOI: 10.1177/0192623315621192
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase Inhibition Causes Reversible Intestinal Toxicity in Mice with a Therapeutic Index < 1

Abstract: Activated Wnt/β-catenin signaling is frequently associated with colorectal cancer. Wnt inhibitors, including tankyrase inhibitors, are being explored as potential anticancer agents. Wnt signaling is also critical for intestinal tissue homeostasis, and Wnt inhibitors have been shown to cause intestinal toxicity in mice by affecting intestinal stem cells. This study sought to characterize the intestinal toxicity of tankyrase inhibitors, including reversibility, and to assess their therapeutic index. Novel tankyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 34 publications
(66 reference statements)
1
83
0
1
Order By: Relevance
“…Waaler et al demonstrated the antitumoral effect of inhibiting tankyrase in a model of colorectal adenoma and adenocarcinoma [70]. Potential adverse events of this therapy include diarrhea and intestinal toxicity [71]. Tankyrase inhibition has been shown to revert resistance to PI3K and AKT inhibitors in colorectal cancer patient-derived sphere cultures and mouse tumor xenografts [72].…”
Section: Wnt Inhibitors In Clinical Developmentmentioning
confidence: 99%
“…Waaler et al demonstrated the antitumoral effect of inhibiting tankyrase in a model of colorectal adenoma and adenocarcinoma [70]. Potential adverse events of this therapy include diarrhea and intestinal toxicity [71]. Tankyrase inhibition has been shown to revert resistance to PI3K and AKT inhibitors in colorectal cancer patient-derived sphere cultures and mouse tumor xenografts [72].…”
Section: Wnt Inhibitors In Clinical Developmentmentioning
confidence: 99%
“…A significant hurdle to the clinical development of WNT inhibitors is overcoming the on-target toxicity that results from effects on the WNT-dependent intestinal stem cells that drive normal gastrointestinal (GI) homeostasis (24, 25). Such dose-limiting on-target toxicities have been observed using both Tankyrase and Porcupine inhibitors (23, 26, 27), with continuous dosing of both classes of small molecules disrupting normal GI structure and function. Thus, there appears to be only a limited therapeutic window for Porcupine and TANKi, which might ultimately limit their clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Although suppression of Wnt pathway activity with inhibitors targeting the Tankyrase enzymes which indirectly control β-catenin abundance by regulating the stability of its destruction complex is anticipated to have a poor therapeutic index, porcupine inhibitors appear to be relatively well tolerated [8, 9]. Thus, Porcn inhibitors such as WNT974 enable a variety of preclinical studies focused on Wnt signaling while limiting the potential influence of unwanted side effects on test outcomes.…”
Section: Introductionmentioning
confidence: 99%